Fluorescent Probes Visualize Phytohormone: Research Status and Opportunities - Liu, Yaming; Liao, Anjing; Chen, Shunhong; Xu, Ying; Zhou, Jing-Jiang; Wu, Jian (Journal of agricultural and food chemistry, 2024)
Phytohormones, as crucial regulatory factors in plant growth and development, have garnered increased interest in improving crop stress resistance. It is essential to comprehend the distribution of phytohormones in plants to assess their health status and investigate their functions. This knowledge also serves as a guide for developing and using plant growth regulators. The advancement of fluorescent probe technology, along with the wide range of fluorophores and improvements in imaging methods, has made it a successful approach for monitoring phytohormones in plants. This technique has been confirmed to be effective in plants, particularly in detecting the response of fluorescent probes to phytohormones. In this Perspective, we highlight the utility of fluorescent probes in measuring and visualizing the distribution of phytohormones in plants under external stress. However, the visualization of phytohormones with high spatial resolution and the achievement of high biocompatibility in living plants have posed significant challenges for researchers. Nonetheless, there are also many untapped opportunities in this field. This paper seeks to delve into the potential for further discussion on the subject.